2014
DOI: 10.4046/trd.2014.76.3.120
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin and Wogonin Regulate Epidermal Growth Factor Receptor Signaling Pathway Involved in MUC5AC Mucin Gene Expression and Production from Cultured Airway Epithelial Cells

Abstract: BackgroundWe investigated whether wogonin and apigenin significantly affect the epidermal growth factor receptor (EGFR) signaling pathway involved in MUC5AC mucin gene expression, and production from cultured airway epithelial cells; this was based on our previous report that apigenin and wogonin suppressed MUC5AC mucin gene expression and production from human airway epithelial cells.MethodsConfluent NCI-H292 cells were pretreated with wogonin or apigenin for 15 minutes or 24 hours and then stimulated with ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
(34 reference statements)
3
8
0
Order By: Relevance
“…The isoflavone genistein was previously shown to inhibit pyocyanin-induced IL-8 secretion (85), likely via genistein's ability to inhibit tyrosine kinase activity (69, 86 -88). We observed induction of IL-8 after treating 16HBE or Calu-3 ALIs with 25 M pyocyanin for 24 h. Apigenin (89 -91), wogonin (91)(92)(93)(94), and tangeritin (95)(96)(97) have previously also been shown to inhibit tyrosine kinases, whereas chrysin has a less inhibitory effect (88,98). Fitting with these prior observations, pyocyanin-induced IL-8 secretion was reduced in the presence of apigenin, wogonin, and tangeritin but not chrysin ( Fig.…”
Section: C and D)supporting
confidence: 79%
“…The isoflavone genistein was previously shown to inhibit pyocyanin-induced IL-8 secretion (85), likely via genistein's ability to inhibit tyrosine kinase activity (69, 86 -88). We observed induction of IL-8 after treating 16HBE or Calu-3 ALIs with 25 M pyocyanin for 24 h. Apigenin (89 -91), wogonin (91)(92)(93)(94), and tangeritin (95)(96)(97) have previously also been shown to inhibit tyrosine kinases, whereas chrysin has a less inhibitory effect (88,98). Fitting with these prior observations, pyocyanin-induced IL-8 secretion was reduced in the presence of apigenin, wogonin, and tangeritin but not chrysin ( Fig.…”
Section: C and D)supporting
confidence: 79%
“…Flavonoids are widely distributed secondary metabolites and currently consumed in large amounts in the daily diet with anti‐inflammatory, antilipidemic, antihyperglycemic, antiviral, hepatoprotective, gastric antiulcer, cardioprotective, neuroprotective, antioxidant, and anticancer actions (Romano et al , ). The flavonoids luteolin (Lee et al , ), apigenin, and wogonin (Kim et al , ; Sikder et al , ) were reported to significantly inhibit stimulated MUC5AC secretion, production, and gene expression at concentration ranges of 5–20 μM via regulation of the NF‐κB signaling pathway. In the present study, 7,4′‐DHF at 10 μM showed similar MUC5AC inhibitory effects via regulation of not only NF‐κB but also HDAC2 and STAT6 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids are natural compounds found in many plants and vegetables. They have been shown to possess a range of effects on biological systems . Apigenin (Figure ) belongs to the flavone subclass of flavonoids.…”
Section: Introductionmentioning
confidence: 99%
“…They have been shown to possess a range of effects on biological systems. [16,17] Apigenin (Figure 1) belongs to the flavone subclass of flavonoids. Apigenin has shown promising effects in the treatment of various cancers.…”
Section: Introductionmentioning
confidence: 99%